Overcoming barriers and ethical challenges in implementing intelligent tutoring systems in Ghanaian higher education - Moses Kumi Asamoah; Jessica Amarteifio (Discover Education)
Abstract This systematic review explores the use of Intelligent Tutoring Systems (ITS) in fostering creativity, innovation, and personalized learning experiences among university students in Ghana. The review also examines the challenges associated with the implementation of ITS, along with the ethical considerations involved. Employing an interpretive case study methodology, the research draws on five academic databases, ensuring a comprehensive and extensive search process. A strategic search, incorporating key terms and Boolean operators, was conducted to identify relevant publications from 2019 to 2024. Following the PRISMA guidelines, 15 peer-reviewed articles focused on ITS in the context of Ghanaian higher education were selected for analysis. The findings confirm that AI tools, particularly ITS, have the potential to enhance creativity, promote innovative behaviors, and support personalized learning pathways. However, the review also uncovers significant challenges, such as infrastructural limitations, gaps in digital literacy, and issues related to the integration of AI technologies in educational settings. In addition, the study highlights several ethical concerns, including ensuring equitable access to ITS, addressing algorithmic biases, and preserving academic integrity. To mitigate these challenges, the review advocates for a balanced approach to ITS integration, emphasizing the need for robust IT infrastructures that ensure consistent access to reliable hardware and software. By adopting such an approach, educational institutions can harness the full potential of ITS to improve learning outcomes while simultaneously addressing the associated risks and ethical dilemmas.